Environmental and Social Risk Factors in the Event of Dengue Hemorrhagic Fever (DHF) in the Work Area of Jiwan Health Center, Madiun Regency - Sari, Mardiana Indah; Rahardjo, Mursid; Astorina Yunita Dewanti, Nikie (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
In the past three years, the Jiwan Health Centre's area has had the highest dengue fever incidence in Madiun Regency. This area still has many water puddles that serve as mosquito breeding grounds. The Jiwan Health Center reported 40 cases and 2 deaths in 2019, 6 cases in 2020, and 16 cases in 2021. This study aimed to identify environmental and social risk factors linked to dengue fever cases in this region. We used an analytical observation method, including a case-control study, and analyzed data with the chi-square test, using probability sampling. A study that looked at just one variable found that air temperature (36.3%), humidity (83.3%), house index (68.8%), container index (41.3%), the lack of mosquito larvae observer cadres (87.5%), fogging activity (55%), and DHF PSN activity (27.5%) were all dangerous. Bivariate test results showed a correlation between the container index (p = 0.000) and fogging activities (p = 0.042) with DHF incidence. There was no significant connection between dengue incidence, air temperature (p = 0.642), humidity (p = 1.000), house index (p = 0.335), jumantic cadre activities (p = 0.737), or PSN DHF activities (p = 0.453). Environmental and social factors, such as positive larvae presence and fogging activities, contribute to the dengue fever incidence in the Jiwan Health Center's area. For the past three years, this area has consistently had the highest dengue fever cases in Madiun Regency, primarily due to persistent mosquito breeding sites.